Genocidio, concepto invisibilizado en los libros de textos de geografía - Nin, María Cristina (Geographicalia, 2020)
This work analyzes the editorial proposals of Geography that are available in Argentina for secondary education worldwide. The focus of the analysis is carried out from the genocidal processes of the XX and XXI century. School texts are a tool and source of consultation for students, but their interpretation and access to knowledge require the mediation of teachers. From the paradigm of a critical Geography, inspiring the defense of human rights and committed to issues relevant to society, the results of the analysis of books on geography editorial proposals, and interviews with teachers are presented.
Keywords: Geography. Teaching. Genocides. Textbooks. Teachers